The Open Education Librarian – Would you Like to Become One? - Corti, Paola; Meen, Kristopher; Bustillo, Marta; Peignen, Celine; Buist-Zhuk, Mira (Ukrainian State University of Science and Technologies, Dnipro, 2022)
ENG: Open Educational Resources (OER) are learning, teaching, and research materials in any format and on any medium (digital or otherwise) that are in the public domain or protected by copyright, released under an open license that permits free access, reuse, repurposing, adaptation, and other distribution without restriction. Librarians can perform many different functions in open education, in addition to providing access to resources, they can be representatives of OER in their institutions, contribute to the formation of open education policy, provide practical support in the creation of open educational resources and much more.

UKR: Відкриті освітні ресурси (OER) – це матеріали для навчання, викладання та досліджень в будь-якому форматі й на будь-якому носії (цифровому або іншому), які знаходяться в суспільному надбанні або охороняються авторським правом, видані за відкритою ліцензією, котра дозволяє безкоштовний доступ, повторне використання, перепрофілювання, адаптацію та поширення іншими способами без обмежень. Бібліотекарі можуть виконувати багато різних функцій у відкритій освіті, окрім надання доступу до ресурсів, вони можуть бути представниками OER у своїх установах, робити внесок у формування політики щодо відкритої освіти, надавати практичну підтримку у створенні відкритих освітніх ресурсів та багато іншого.
Бібліотекар відкритої освіти – чи хотіли б ви ним стати?
Keywords: open education; open education librarians; Open Educational Resources; відкрита освіта; бібліотекарі відкритої освіти; відкриті освітні ресурси